The silent influence: experimental validation of cultural unconscious and its psychological impact through Chinese archetypal imagery - Wang, Wenlong; Shen, Heyong; Zhang, Xin; Wen, Langyi (Frontiers in Psychology, 2025)
This paper empirically confirms Henderson's theory of cultural unconscious which is a psychic layer mediating between collective unconscious and the personal unconscious. We particularly tested the effect of high-valence Chinese archetypal imagery on cognition. A multi-method experimental design was applied to three studies to demonstrate unconscious activation: (1) Reaction Time task proved faster cognitive processing to the exemplary archetypal images than the nonrepresentative ones (study1); (2) Supraliminal Priming followed by a situational choice task proved that there was a significant, unconscious bias of behavioral choices that followed the symbolic meanings of the images (study2); (3) Rigorous Subliminal Priming demonstrated that cultural unconscious could be activated to influence semantic alignment in a word-choice task, even outside of conscious awareness (study3). These data provide solid, quantitative proof that the cultural unconscious is an operatively effective psychological structure, bridging depth psychology concepts with contemporary cognitive science.